Strong adsorption of Polychlorinated Biphenyls by processed montmorillonite clays: Potential applications as toxin enterosorbents during disasters and floods. (December 2019) - Wang, Meichen; Safe, Stephen; Hearon, Sara E.; Phillips, Timothy D.
Abstract: Polychlorinated biphenyls (PCBs) have been detected as prevalent environmental contaminants in water, food and biota. Previous studies in vitro have shown that a variety of sorbent materials, including carbon, can sorb PCBs; however, PCB sorbents that can be added to food or drinking water to decrease toxin bioavailability in humans and animals have not been reported. To address this problem, we have developed broad-acting and highly effective sorbents for PCBs using montmorillonite clays reported to be safe for consumption in animals and humans. In this study, calcium montmorillonite clays were acid processed (APMs) and the interactions of six PCB congeners (PCB 77, 126, 153, 157, 154 and 155) on the surfaces of APMs were characterized. Computational models and isothermal analyses were used to derive surface capacities and affinities, delineate mechanisms and predict the thermodynamics of sorption. To confirm the safety and predict the efficacy of APMs against individual PCBs and common mixtures (Aroclors 1254 and 1260), we have also used a living organism ( Hydra vulgaris ) that is sensitive to toxins. APMs significantly protected hydra against the toxicity of PCBs and Aroclors. This finding was supported by studies showing tight binding; high capacity, affinity, and enthalpy; and a low therapeutic dose. Graphical abstract: Image 1 Highlights: PCBs and mixtures were chemisorbed onto the surfaces of processed clays (APMs). APMs showed high capacities, affinities, enthalpies and efficacy for PCBs. APMs (at low doses) protected against PCBs and Aroclors in vivo . Steric effects and ortho chlorine substitution were important for PCB sorption. Low doses of APMs could reduce PCB exposures in humans and animals. Abstract : Capsule: APMs were shown to be broad-acting sorbents that can tightly bind PCBs and mixtures of PCBs, mitigating toxicity in a living organism and reducing potential exposures to humans and animals.